A Dense and Direct Approach to Visual Servoing Using Depth Maps - Teuliere, Celine; Marchand, Eric (IEEE transactions on robotics, 2014)
This paper presents a novel 3-D servoing approach using dense depth maps to perform robotic tasks. With respect to position-based approaches, our method does not require the estimation of the 3-D pose (direct), nor the extraction and matching of 3-D features (dense), and only requires dense depth maps provided by 3-D sensors. Our approach has been validated in various servoing experiments using the depth information from a low-cost Red Green Blue-Depth (RGB-D) sensor. Positioning tasks are properly achieved despite noisy measurements, even when partial occlusions or scene modifications occur. We also show that, in cases where a reference depth map cannot be easily available, synthetic ones generated with a rendering engine still lead to satisfactory positioning performances. Application of the approach to the navigation of a mobile robot is also demonstrated.